Diagonal gaits in the feathertail glider Acrobates pygmaeus (Acrobatidae, Diprotodontia): Insights for the evolution of primate quadrupedalism. Issue 86 (September 2015) - Karantanis, Nikolaos-Evangelos; Youlatos, Dionisios; Rychlik, Leszek
Abstract: Research on primate origins has revolved around arboreality and, more specifically, the adaptations that are linked to safe navigation in the fine-branch niche. To this end, extant non-primate mammals have been used as models to assess the significance of these adaptations. However, the size of these models is larger than that estimated for early primates. In contrast, the feathertail marsupial glider Acrobates pygmaeus, with a body mass of 12 g, a clawless opposable hallux, and terminal branch feeding habits appears more suited to modeling behavioral adaptations to the small branch milieu. Analysis of video recordings of 18 feathertail gliders walking on poles of variable diameter and inclination revealed that they preferentially used diagonal sequence gaits, fast velocities and low duty factors. Diagonal gaits did not correlate to duty factor, but increased as substrate size decreased, and from descending to ascending locomotion. Furthermore, the duty factor index increased in more diagonal gaits and ascending locomotion. Finally, velocities were lower on smaller substrates, and were mainly regulated by stride frequency and, to a lesser degree, stride length. Feathertail glider gaits displayed noteworthy behavioral convergences with primate quadrupedalism, but some of these results need additional investigation. Despite any discrepancies, these features appear to be favorable for quadrupedal progression on small branches, providing a selective advantage for navigating within a fine branch niche and highlighting the importance of small body size in early primate evolution.